13C nuclear magnetic resonance studies of anaerobic glycolysis in suspensions of yeast cells. - den Hollander, J A (1979)
Anaerobic glycolysis in Saccharomyces cerevisiae has been studied by 13C NMR at 90.5 MHz. [1-13c]Glucose and [6-13C]glucose were fed to suspensions of yeast cells. Time courses for concentration changes of the starting material, of courses for concentration changes of the starting material, of the intermediate fructose 1,6-bisphosphate (Fru-P2), and of the end products, ethanol and glycerol, have been followed with 1-min time resolution. The glucose uptake was well fitted by a Michaelis-Menten model, assuming competition of alpha- and beta-glucose for the same site. The Km for the uptake was found to be 10 mM for beta-glucose and 5 mM for alpha-glucose. The concentration of Fru-P2 showed an initial oscillation before it reached a co,stant level. The 13C label, introduced only as [-13C]- or [6-13C]glucose, was observed in Fru-P2 in both the C1 and C6 positions, simultaneously. From the relative intensities of the C1 Fru-P2 and C6 Fru-P2 peaks in the presence of [1-13C]- and [6-13C]glucose, in vivo kinetic information was obtained about the aldolase-triosephosphate isomerase triangle. We found that under the conditions of these experiments the ratios of backward to forward velocities through aldolase and triosephosphate isomerase were 0.9 +/- 0.1 and 0.8 +/- 1, respectively, indicating they were close to equilibrium.